High-precision fiber optic liquid level sensor based on fast Fourier amplitude demodulation in a specific range of spectrum - Wang, Shun (2022)
This study presents a fiber optic liquid level sensor (FOLLS) by acquiring information from the amplitude of spectral fast Fourier transform (FFT) in a specified narrow wavelength range. The sensing light path is simply formed by embedding a section of Panda-type polarization-maintaining fiber (PMF) into the sensing arm of a conventional Michelson interferometer (MI) structure. The output composite spectrum consists of two parts: the fine interference fringes due to MI optical path difference (OPD) and the envelope fringes stemming from the PMF's birefringence. By applying liquid level variations on the sensing structure, shifts in envelope wavelength indicate a sensitivity of −0.193 nm/cm, and a liquid level resolution of 1 mm can be easily acquired. Furthermore, by demodulating the amplitude after spectral FFT in a specific narrow wavelength range, and intensity sensitivity of 1.906 dB/cm is achieved, leading to a greatly improved overall resolution of 0.03 mm in liquid level measurement. Besides, the sensing element is sealed and packaged by two sheets of silicone rubber, which can be thrown into liquid when in use, thus easing the sensor installation. Moreover, due to the proposed demodulation method, the sensor is insensitive to the light source power jitter, reference arm phase shift and optical spectral analyzer wavelength shift. Therefore, the merits of the proposed sensor include high precision, high stability, ease of installation, which are beneficial in pore water pressure and liquid level monitoring.